Behavioural lifestyle factors, physical health-related fitness and cardiometabolic disease risk in women from a low socio-economic urban community in Stellenbosch (Western Cape) - Dickie, Kasha Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD Sport Sc)--Stellenbosch University, 2020.